Customer satisfaction & perception towards service quality a case of TH properties, Enstek Nilai / Nurfatihah Sharudin - Sharudin, Nurfatihah (Faculty of Business and Management, 2013)
This research is study on the customer satisfaction and perception towards service quality offered by TH Property Sdn Bhd. TH Properties Sdn Bhd are located at Enstek Nilai currently it core business included services such property development, construction, project management and facilities management. In TH Properties, Enstek Nilai it more focused on offer services such as selling land for the developer and houses development. This research helps in determine what factor will influence customer satisfaction and perception which relates to the service quality that been offered by the organization. The dimension of SERVQUAL will help further in determine in what areas customer satisfy with the service given. SERVQUAL function as measure the customer expectation and assumption towards the company’s service quality. SERVQUAL originally consist of 5 dimensions which include reliability, tangibles, responsiveness, assurance and empathy. The model will help to evaluate the customer’s service experience and help organization to improve service in several aspects.